Antimicrobial and therapeutic properties of bacteriocins from Lactobacillus casei isolated from goat milk: Bacteriocin from goat milk isolate - Koori Parambil, Jumaila; A, Vijaya Chitra; Nettoor Veettil, Vajid; Ali Kadavath, Shamla (Cellular and Molecular Biology, 2025)
Lactic acid bacteria (LAB) bacteriocins are renowned for their broad spectrum of antimicrobial activity. These organisms are generally recognized as safe and are predominantly utilized in food preservation, effectively suppressing harmful bacteria. The present study aims to isolate LAB from goat milk, purify bacteriocins and analyze its therapeutic applications. Of the 26 isolates, isolate GO3 showing enhanced antimicrobial activity against food-borne pathogens was identified using 16s rRNA sequencing. The organism was identified as Lactobacillus casei GO3 with 100% similar to Lactobacillus casei strain NR115322.1. Cystathionine gamma-synthase gene (MetB) with high homology to Lacticaseibacillus casei strain MetB gene was detected in the isolate GO3. The partially purified bacteriocin from Lactobacillus casei GO3 demonstrated a broad spectrum of antibacterial activity, achieving 76.4% inhibition against Gram-positive B. subtilis and 46.2% against Gram-negative Salmonella typhi and antifungal activity, with maximum against Phytophthora infestans (47.7%) and a minimum against Fusarium oxysporum (42.2%). In addition to its antimicrobial activities, the bacteriocin demonstrated significant anti-inflammatory, α-amylase inhibition, antioxidant and anticancer activity. Further studies are required to analyze its mechanism of action and potential therapeutic applications in real-world scenarios.